INFLUENCE OF DIGITAL ACCOUNTING AND DIGITAL LITERACY ON FINANCIAL REPORT PREPARATION WITH USER ABILITY AS A MODERATION - Alfiyan; Sri Anik; Imam Prayogo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Islamic boarding schools (pondok pesantren) play a crucial role in the rapid development of MSMEs. This study was conducted at the Al-Bismi Islamic Boarding School Association to analyze the influence of digital accounting and digital literacy on financial report preparation, with user capability as a moderating variable. This research employs an explanatory research method with a quantitative approach. Hypothesis testing was conducted using Partial Least Squares (PLS). The study's subjects include Islamic boarding school administrators and students managing MSMEs owned by the pesantren. The variables examined in this study include digital accounting, digital literacy, financial report preparation, and user capability. The results indicate that digital accounting and digital literacy significantly influence financial report preparation. However, user capability does not moderate the effect of digital accounting on financial report preparation, nor does it moderate the effect of digital literacy on financial report preparation.